(untitled) (Research, Society and Development, 2022)
Agribusiness is fundamental to Brazil’s economy. In 2020, it reached a share of 26.6% in the Brazilian GDP, and this is due to the various sectors encompassed by agribusinesses, such as banks that provide credit, input industry (fertilizers, pesticides, specialties, seeds), agricultural implements, and laboratories. In this context, this research aims to understand the barter operations transformation of an agribusiness company in a city in the south of Minas by monitoring the implementation of digital CPR. We also present the technology used, highlighting the pros and cons of this transformation. Hence, through a case study, we researched a holding of agricultural inputs, where one of its companies is in the south of Minas Gerais. This holding company operates throughout Brazil in the agribusiness sector in general. The as-is process was evaluated (as it is), monitoring and analyzing possible improvements in making non-electronic guarantees applied in the barter sector. After the implementation of digital CPR (to-be), it was possible to verify a significant reduction in the total time of the process, although there is still some resistance in the small farmers for the adoption of digital CPR.